An assessment of clients' knowledge of family planning in Matlab - Hashima-E-Nasreen; Chowdhury, Mushtaque; Bhuiya, Abbas; Rana, AKM Masud; Caldwell, Indrani Pieris (BRAC Research and Evaluation Division (RED), 2019)
The study aimed to assess the level of effective knowledge of women on different family planning methods to see the impact of quality of care. The study was carried out in two villages chosen from ICDDR,B intervention and comparison areas of Matlab thana where BRAC's Rural Development Programme (RDP) has also been working since 1992. From both the areas 600 women of reproductive age were randomly selected and interviewed. The findings reveal that in the MCH-FP area 56% of women practiced family planning while only 33% did so in the comparison area. In both the areas the main methods used were pills and injectables. Regarding the knowledge of contraceptives, most women in the MCH-FP area were able to name five modem methods while the majority in the comparison area could name only three methods. Virtually all women in both the villages could describe the nature of the pill and ligation while many had no idea about IUD and condom. Correct categorization of methods as temporary or permanent was found to be higher in the MCH-FP area than in the comparison area. The study found that women in both the areas had little or no knowledge of the specific indications of all methods. The majority of women in the MCH-FP area knew about proper use of pill, injection and condom compared to those in the comparison area where none had complete knowledge regarding any method. However, even in the MCH-FP area women did not know what to do if two pills were missed. The nature and the function of the brown tablets were not known to the women in the comparison area but some women in the MCH-FP area had some idea of the furmm. . In the MCH-FP area 78.4 % of the women knew the specific date of menstrual period from which injection should be started compared to the comparison area where only some of them knew about that. The majority of respondents in both the areas knew that it should be taken regularly at an interval of three months on a· fixed date. which was significantly higher in the MCH-FP area. The study found that maj~rity of women in the MCH-FP area knew the exact time and frequency of using condom compared to the comparison area where only a few .knew that. This is not surprising given that only a small proportion of women in the comparison area ever heard of condoms and that none of the couples were using it. \Vomen had no knowledge about the timing of insertion of IUD, but only that it had to be replaced periodically at an interval of2-4 years. - Women's general perception about the mechanism of action of the different methods was that they act by damaging the sperm or ovum. Women had no clear idea about the advantages of any of the methods. It was found that most of the women in the MCH-FP area were interested in injection, as the main advantage was that one injection provided three months' protection and maintained privacy (as it was administered like any other injection). This was specially appreciated by those who were shy about using contraceptives. Women had little knowledge of the side-effects of contraceptive methods. The commonly mentioned side-effects of pill and injection were: giddiness, weakness, headache, and irregular and heavy menstrual bleeding. Some respondents mentioned that injection caused prolonged amenorrhoea which in tum caused bodyache, and burning sensation in hands and feet. The women in the MCH-FP area had misconceptions about condoms such as that it might cause genital ulcer. The side-effects of ligation were more often assumed than actually experienced.